UZNANIE ZA ZMARŁEGO I STWIERDZENIE ZGONU (GENEZA, ROZWÓJ INSTYTUCJI I POSTĘPOWANIA) - Bartoszewicz, Anna (Zeszyty Prawnicze, 2017)
The Origins and Development of the Law on the Presumption of Death and Declarations of Death Summary The article presents the history of the presumption of death and declaration of death. It provides an insight into the relevant concepts of the Roman law as well as chosen examples of the laws of the ancient Middle East. It also focuses on the Polish and foreign laws which were in force on the historically Polish territory during the period of the country’s loss of independence (1795-1918). It identifies the origins of the presumption of death and declaration of death in the Polish law and examines their development (including the relevant civil procedurę provisions) until 1964, when the present civil code and civil procedurę code came into force. By presenting and comparing the laws governing the presumption of death and declarations of death, the author highlights the different approaches of the laws that applied at the time of the loss of independence: those of Prussia, Russia, Austria and the Polish Kingdom, as well as the law in effect in the Grand Duchy of Warsaw. The article also considers the extent to which the laws introduced after Poland regained independence in 1918 were influenced by the foreign regimes previously in force. The gradual developments in the law following the Second World War are presented against the background of the major changes in Polish civil law over the same period, which occurred mainly via the codifications of the law in the civil code and the civil procedure code.